Postnatal Smad3 Inactivation in Murine Smooth Muscle Cells Elicits a Temporally and Regionally Distinct Transcriptional Response - Bramel, Emily E.; Creamer, Tyler J.; Saqib, Muzna; Camejo Nunez, Wendy A.; Bagirzadeh, Rustam; Roker, LaToya Ann; Goff, Loyal A.; MacFarlane, Elena Gallo (Frontiers in Cardiovascular Medicine, 2022)
Heterozygous, loss of function mutations in positive regulators of the Transforming Growth Factor-β (TGF-β) pathway cause hereditary forms of thoracic aortic aneurysm. It is unclear whether and how the initial signaling deficiency triggers secondary signaling upregulation in the remaining functional branches of the pathway, and if this contributes to maladaptive vascular remodeling. To examine this process in a mouse model in which time-controlled, partial interference with postnatal TGF-β signaling in vascular smooth muscle cells (VSMCs) could be assessed, we used a VSMC-specific tamoxifen-inducible system, and a conditional allele, to inactivate Smad3 at 6 weeks of age, after completion of perinatal aortic development. This intervention induced dilation and histological abnormalities in the aortic root, with minor involvement of the ascending aorta. To analyze early and late events associated with disease progression, we performed a comparative single cell transcriptomic analysis at 10- and 18-weeks post-deletion, when aortic dilation is undetectable and moderate, respectively. At the early time-point, Smad3-inactivation resulted in a broad reduction in the expression of extracellular matrix components and critical components of focal adhesions, including integrins and anchoring proteins, which was reflected histologically by loss of connections between VSMCs and elastic lamellae. At the later time point, however, expression of several transcripts belonging to the same functional categories was normalized or even upregulated; this occurred in association with upregulation of transcripts coding for TGF-β ligands, and persistent downregulation of negative regulators of the pathway. To interrogate how VSMC heterogeneity may influence this transition, we examined transcriptional changes in each of the four VSMC subclusters identified, regardless of genotype, as partly reflecting the proximal-to-distal anatomic location based on in situ RNA hybridization. The response to Smad3-deficiency varied depending on subset, and VSMC subsets over-represented in the aortic root, the site most vulnerable to dilation, most prominently upregulated TGF-β ligands and pro-pathogenic factors such as thrombospondin-1, angiotensin converting enzyme, and pro-inflammatory mediators. These data suggest that Smad3 is required for maintenance of focal adhesions, and that loss of contacts with the extracellular matrix has consequences specific to each VSMC subset, possibly contributing to the regional susceptibility to dilation in the aorta.